Effects of Online Tools utilization on thinking skills: Afghanistan student's Perceptions - Mohammad Basir, Bakhtyari; Hafizoah, Kassim (International Science Congress Association, 2014)
Online technology plays an important role in teaching and learning especially to provide variety into students’ learning experiences. In Afghanistan, to embrace the technologically-driven learning, the Ministry of Higher Education (MoHE) encourages all universities to use technology for teaching and learning. It is hoped that with such effort, technology is able to assist students’ learning particularly to enhance their thinking skills. Although the challenge has been well-accepted and implemented, it is essential to investigate whether this move has the positive effects it aimed for. This study therefore investigated Afghanistan university students’ perceptions of online tools utilization on their thinking skills. 217 questionnaires were distributed, and 35 of the participants volunteered to be interviewed. The results generally show positive perceptions of the effects of using online tools on thinking skills. Participants also believed that online tools have helped developed their lower-order better than their higher-order thinking skills. The findings proposed providing training programs for teachers and students to use online tools effectively for better learning experience where thinking skills particularly higher-order thinking can be enhanced.